THE DIFFICULTIES OF STUDENTS AT THE SECOND YEAR OF SMA St. THOMAS 3 MEDAN IN TRANSLATING ENGLISH IDIOMS INTO INDONESIAN - Sinurat, Fitri Susi (Kairos English Language Teaching Journal, 2017)
This study deals with the difficulties of students at the second year of SMA St. Thomas 3 Medan in translating idioms English-Indonesian. The objective of this study is to find out the students’ difficulties in translating idioms from English to Indonesian. The sample of this study was the students of class XI IPA-2 SMA St. Thomas 3 Medan. This study used descriptive qualitative research. The data were collected by giving a test which consists of 35 items of English idioms that must be translated to Indonesian. Based on the data analysis, the students’ difficulties generally are mostly caused by lacking of vocabularies so they were no able to understand the meaning clearly. Another students’ difficulties are in understanding the context of the sentence in each items, guessing the exact meaning of an idiom in the sentence, and also in choosing an appropriate diction to replace the word of an idiom. The result of this study showed that the second year students of SMA St. Thomas 3 Medan have some difficulties in translating idioms from English to Indonesian. They need more teaching about the way of translating and the teacher should give more attention to train the students in translating idioms.